Discovery of Aporphine Analogues as Potential Antiplatelet and Antioxidant Agents: Design, Synthesis, Structure–Activity Relationships, Biological Evaluations, and in silico Molecular Docking Studies. (8th August 2018) - Sharma, Vashundhra; Jaiswal, Pradeep K.; Kumar, Surendra; Mathur, Manas; Swami, Ajit K.; Yadav, Dharmendra K.; Chaudhary, Sandeep
Abstract: To explore the potential of aporphine alkaloids, a novel series of functionalized aporphine analogues with alkoxy (OCH3, OC2 H5, OC3 H7 ) functional groups at C1/C2 of ring A and an acyl (COCH3 and COPh) or phenylsulfonyl (SO2 Ph and SO2 C6 H4 ‐3‐CH3 ) functionality at the N6 position of ring B of the aporphine scaffold were synthesized and evaluated for their arachidonic acid (AA)‐induced antiplatelet aggregation inhibitory activity and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) free‐radical‐scavenging antioxidant activity, with acetylsalicylic acid and ascorbic acid as standard references, respectively. The preliminary structure–activity relationship related to AA‐induced platelet aggregation inhibitory activity results showed that the aporphine analogues 1‐[1, 2, 9, 10‐tetramethoxy‐6 a, 7‐dihydro‐4 H ‐dibenzo[ de, g ]quinolin‐6(5 H )‐yl]ethanone and 1‐[2‐(benzyloxy)‐1, 9, 10‐trimethoxy‐6 a, 7‐dihydro‐4 H ‐dibenzo[ de, g ]quinolin‐6(5 H )‐yl]ethanone to be the best compounds of the series. Moreover, the DPPH free‐radical‐scavenging antioxidant activity results demonstrated that the aporphine analogues 1, 2, 9, 10‐tetramethoxy‐6‐(methylsulfonyl)‐5, 6, 6 a, 7‐tetrahydro‐4 H ‐dibenzo[ de, g ]quinoline, 2‐ethoxy‐1, 9, 10‐trimethoxy‐6‐(methylsulfonyl)‐5, 6, 6 a, 7‐tetrahydro‐4 H ‐dibenzo[ de, g ]quinoline, 1‐ethoxy‐2, 9, 10‐trimethoxy‐6‐(methylsulfonyl)‐5, 6, 6 a, 7‐tetrahydro‐4 H ‐dibenzo[ de, g ]quinoline, 2, 9, 10‐trimethoxy‐6‐(methylsulfonyl)‐1‐propoxy‐5, 6, 6 a, 7‐tetrahydro‐4 H ‐dibenzo[ de, g ]quinoline, and 1‐(benzyloxy)‐2, 9, 10‐trimethoxy‐6‐(methylsulfonyl)‐5, 6, 6 a, 7‐tetrahydro‐4 H ‐dibenzo[ de, g ]quinoline were the best compounds of the series. Moreover, in silico molecular docking simulation studies of the active analogues were also performed. Abstract : A familiar ring : Functionalized aporphine analogues with alkoxy functional groups at C1/C2 of ring A and an acyl or phenylsulfonyl functionality at the N6 position of ring B of the aporphine scaffold were synthesized and evaluated for their arachidonic acid induced antiplatelet aggregation inhibitory activity and free‐radical‐scavenging antioxidant activity. In silico molecular docking simulation studies of the active analogues were also performed.